RACIAL DISCRIMINATION IN THE CANADIAN CRIMINAL JUSTICE SYSTEM: HOW ANTI-BLACK RACISM BY THE TORONTO POLICE HARMS US ALL - Mensah, Joseph; Firang, David; J. Williams, Christopher; Afrifah, Michelle (Canadian Social Work Review / Revue canadienne de service social, 2021)
Due to the persistent and tenacious practices of anti-Black racism, embedded in White supremacist policing practices, Black and Indigenous people are overwhelmingly overrepresented in the Canadian criminal justice system. Unsurprisingly, a disproportionate number of Black people are killed at the hands of police in Toronto. The Canadian criminal justice system is complicit in perpetuating anti-Black racism through practices of surveillance, carding, and racial profiling. This paper contributes to the analysis of anti-Black racism in the Canadian criminal justice system, emphasizing the circumstances of Black people in Toronto. The goal is to wed the study of Black criminalization with the analysis of anti-Black racism and social stratification in Canada to show how existing patterns of racism and socioeconomic marginalization are reinforced by a White supremacist criminal justice system. The paper offers recommendations to address the issue of anti-Black racism, including the hiring of more Black people in the police force. Conceptually, the paper contributes to our understanding of how anti-Black racism ricochets to hurt us all in society.